Spatial Configuration of Logistics Firms Relative to Cape Town International Airport, South Africa - Masilonyane Mokhele; Tholang Mokhele (Logistics)
Background: A multi-faceted analysis of the positioning of logistics facilities relative to airports is a topical aspect of the interconnections between transport infrastructure and the spatial configuration of economic activities. Regardless of the wide range of studies that exist on the topic, little is known about the logistics catchment of airports. Towards extending the literature, the objective of the paper is to analyse the spatial configuration of logistics firms relative to Cape Town International Airport (CTIA) in South Africa. Methods: The inclination of logistics facilities to locate in industrial areas is widely acknowledged in the literature. As such, the data on the main industrial and economic nodes in the City of Cape Town metropolitan area were obtained from the City of Cape Town municipality and used to ascertain the extent of the industrial areas across the metropolitan area. The resultant geographic information system (GIS) shapefile of the industrial and economic nodes was used to obtain the logistics firms’ data from AfriGIS. Following the cleaning of the data from AfriGIS, ArcGIS 10.8 and QGIS 3.16 were used for spatial analysis (buffer, kernel density and network analysis) to establish the spatial configuration of the logistics firms relative to CTIA. Results: The results showed that of the 985 logistics firms in the metropolitan area, 937 were located within 20 km of CTIA. Furthermore, the kernel density results showed that high density values were found in the environs of the Cape Town central business district (CBD), Port of Cape Town and Milnerton. The results of the network analysis indicated that the furthest firm was 50 km and 64 min away on the shortest route to CTIA, while it was 55 km and 49 min away on the fastest route. Conclusions: Relative to the literature, the results show that CTIA has the potential to facilitate the emergence of a logistics hub at the city or metropolitan scale.